Activity of Lithuanian people‘s militia in neutral territory (1920-1923) - Ereminas, Gintautas (Genocidas ir rezistencija, 2017)
The subject of the article is the protection of civilians, their property and the neutral zone itself by the Lithuanian People’s Militia in the neutral zone established between the Republic of Lithuania and the Polish-occupied Vilnius region during the politically difficult period (1920–1923). Based on the documents of the Chief Headquarters of the People’s Militia of the neutral zone, an attempt is made to reconstruct the activities of the unit that performed the functions of the Border Police of the Republic of Lithuania and fought against the Polish partisans operating in the neutral zone.
Keywords: Lithuania; Poland; Vilnius region; polish occupation; borderland